Organoleptic Test of Layer Cake with Durian Seed Flour - Kadek Deviani Wulandari; Made Hendrayana; I Nyoman Sunada; AA Gd KP Dalem (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
In this study, durian seed flour was processed into layer cake so that it changed the final result of the layer cake in terms of color, aroma, taste and texture. This study aims to determine the quality of the organoleptic test of layer cake with durian seed flour. Data collection methods used in this study were experiments, organoleptic tests, questionnaires, documentation, panelist tests, and Likert scales. After conducting the experiment, it was continued with a panelist test to obtain the results of the organoleptic test from 25 fairly trained panelists. In the test, a questionnaire form was used and the results of the questionnaire were calculated using the Likert scale technique. The results of the organoleptic test in terms of color, aroma, taste and texture obtained an average total of 84% with a very good interpretation. It can be concluded that durian seed flour can be an alternative to rice flour in layer cake.